Author Correction: Is body-weight supported treadmill training or robotic-assisted gait training superior to overground gait training and other forms of physiotherapy in people with spinal cord injury? A systematic review. Issue 4 (April 2018) - Mehrholz, J.; Harvey, L.; Thomas, S.; Elsner, B.
The original article can be found online athttps://doi.org/10.1038/sc.2017.31 .